A qualitative approach to determine the problems and challenges faced by microfinance institution with reference to poverty alleviation: A case of district Bahawal Nagar, Punjab, Pakistan - Iqbal, Zahid; Hussain, Rai Imtiaz; Ali, Muhammad; Sohail, Hamna; Ali, Hafiz Fawad (International Journal of Economics and Financial Issues, 2020)
This study aims are to identify the factors that create hurdle in poverty reduction with reference to loan provided by the Microfinance Institutions (MFIs) to the destitute people of District Bahawalnagar. In this study questions regarding Utilization of Loan for Immediate Needs (ULIM), Miss Match of Loan Amount (MMLA), Customer Capacity for Utilizing Loan (CCUL) and Utilization of Loan by Addict Customer (ULAC) were asked to the respondent through face to face interview. After than all interview was transcript in MS Excel and important themes were identified with their percentage of frequencies. In this study 12 important themes through four questions were identified. Important themes that are identified through ULIN is the Spending loan amount on construction, marriages and health & education, whereas the compatibility of loan amount, high interest rate and high processing fee are the themes that are derived from MMLA. Another question that is CCLU, through this lack of business education, business experience and business skill were derived and taking loan by drugs addicts, gambler and using loan on recreational goods were identified through ULAC questions. All these factors will be shared with all MFIs that are working for poverty alleviation so that a milestone of poverty elimination will be achieved by controlling these factors through proper planning and formulating policies regarding these factors. Keywords: Microfinance Institutions, Poverty Alleviation, Pakistan JEL Classifications: G21, I32 DOI: https://doi.org/10.32479/ijefi.10232